(untitled) (CIPEEX, 2025)
INTRODUCTION: Ineligibilities are part of negative political rights, consisting of rules that prevent certain citizens from exercising passive electoral capacity. They are divided into absolute, provided exclusively in the Federal Constitution, such as those who are not registered to vote and illiterates (FC, art. 14, § 4); and relative (FC, art. 14, §§ 5 to 9), which may be provided for in constitutional and infraconstitutional rules, classified as functional, reflexive, military, and legal ineligibilities. In the latter group, the Complementary Law No. 135/2010 (“Clean Record Law”) stands out. OBJECTIVE: This paper aims to analyze the cases of ineligibility established by Complementary Law No. 135/2010, as well as its impacts on the scope of negative political rights, with an emphasis on the principle of electoral morality. METHOD: A bibliographical and documentary research was carried out, based on technical studies by the Superior Electoral Court (TSE), the Electoral Justice, and legal doctrines. The interpretative method is presented through the compilation of direct documentation studies, under a qualitative approach. RESULTS: The Clean Record Law, a popular initiative, reformed Complementary Law No. 64/1990 by expanding the cases of ineligibility based on candidates’ prior conduct. Among the innovations, the following stand out: extension of the ineligibility period to eight years; inclusion of new crimes; removal of the requirement for a final and unappealable judgment (a decision by a collective judicial body is sufficient); and the application of ineligibility to situations such as simulated marital separation, illegal vote buying, and ethical-professional sanctions. CONCLUSION: The Clean Record Law represents a milestone in strengthening democratic institutions by establishing stricter moral criteria for holding elected office, promoting greater integrity in the electoral process.